Microstructure of Parapapillary Atrophy: Beta Zone and Gamma Zone - Dai, Yi; Jonas, Jost B.; Huang, Haili; Wang, Min; Sun, Xinghuai (Investigative ophthalmology & visual science, 2013)
To examine the morphologic features of parapapillary atrophy by using enhanced depth imaging optical coherence tomography (EDI-OCT) and color fundus photographs. The clinical observational comparative study included 80 normal eyes of 46 subjects and 80 eyes of 46 patients with primary open-angle glaucoma. Both groups did not vary significantly in axial length (P = 0.62) and refractive error (P = 0.30). Color fundus photographs and cross-sectional B-scan images obtained by EDI-OCT were examined. On the EDI-OCT images, we measured a gamma zone defined as the region between the temporal disc margin to the beginning of Bruch's membrane, and a beta zone defined as Bruch's membrane without retinal pigment epithelium. The gamma zone (mean area: 1.13 ± 2.04 mm(2)) was significantly associated with longer axial length (P < 0.001; standardized coefficient beta: 0.48), longer vertical disc diameter (P < 0.001; beta: 0.43), older age (P = 0.008; beta: 0.22), and the absence of glaucoma (P = 0.03; beta: -0.19). The beta zone (mean area: 0.85 ± 0.60 mm(2)) was associated with longer axial length (P < 0.001; beta: 0.39) and the presence of glaucoma (P < 0.001; beta: 0.48). In addition to associations with older age, increasing myopia, and larger disc size, the EDI-OCT-defined gamma zone of parapapillary atrophy was associated with the absence of glaucoma, whereas the EDI-OCT-defined beta zone was associated with the presence of glaucoma. Differentiation between the beta zone and the gamma zone may be clinically useful.